Titanium dioxide and cobalt oxide as a catalyst in catalytic converter for 4-stroke motorcycle engine / Mohibah Musa - Musa, Mohibah (2006)
Motorcycle production has been expanding rapidly over the past several years, especially in the urbanized areas of Malaysia. The sales of a new motorcycle are expected to continue to increase. Motorcycles emit large amount of hydrocarbons (HC), carbon monoxide (CO) and particulate matter. These pollutants have significant adverse health effects and deteriorate environmental quality. The emissions contribute to poorer air quality due to the increasing number of motorcycle. This is especially noticeable in densely populated areas of Malaysia, which relies on motorcycles as an essential means of transportation. To address the serious pollution problems posed by motorcycles, a growing number of countries have implemented or are in the process of implementing motorcycles pollution control programs aimed to reduce harmful emissions from motorcycles engine. Catalytic converter have been developed as a result of these regulations and it is generally recognized to be the most cost-effective way to meet stringent emission standards. Catalytic converter technology uses a metal catalyst to chemically convert the harmful components of the motorcycles exhaust stream in to harmless gases. A “tree ways catalytic material” causes the desired chemical reactions to occur without being consumed. Catalytic converter for 4-stroke motorcycle engine was designed similarly to three-way conversion catalyst (TWC) where that catalytic control system can promotes the reaction of hydrocarbons (HC) and carbon monoxide (CO) with oxygen to form carbon dioxide and water, beside the both reaction above these technology also bring the simultaneous chemical reduction of oxides of nitrogen (NOx) to nitrogen gas. In this study cobalt based titanium dioxide was used as a metal catalyst to replace the precious metal conventionally used in our market. As a substrate woven stainless steel was introduced to replace the role of honeycomb structure. Several testing were conducted, and outstanding comparative performance was obtained using the newly developed catalytic converter